Paradiplomacia eclesiástica e internacionalização de redes evangélicas brasileiras na América do Sul - Santos, Alexandre Felipe Pinho dos (2014)
The present work aims to study the internationalization process of Brazilian Protestant churches, especially in South America, with a focus on Pentecostal branch, as well as the networks of national origin, based on the discussions of geography on religious diffusion. To start the research begins with a thesis, which consists in the belief that the axiological elements such as religion, interfere in the concrete, as in politics and the economy. To support the thesis, research developed based on a general goal, followed by four specific objectives, the overall goal is to understand the system of fixed and flows of Brazilian Pentecostals networks in South America. The first specific aim is to systematize the main theoretical discussions about religion in geography. The second specific aim is to discuss the history of Protestantism in Brazil, from his arrival in the country, to its current process of international diffusion. The third specific objective is to study the dynamics of national broadcast of the main churches Pentecostals who are Evangelical Churches Assemblies of God, the Universal Church of the Kingdom of God and the Church of the Foursquare Gospel. The fourth specific objective is to analyze the internationalization of these same three Brazilian Pentecostal churches. The technical and methodological tools based on theoretical, historical and empirical discussions. Therefore in research are stated patterns of networks, periodization of its expansion, and are created categories of analyzes regarding the internationalization of Brazilian Pentecostal churches.